1977
DOI: 10.1002/prac.19773190204
|View full text |Cite
|
Sign up to set email alerts
|

Versuche an einer neuen Caprolactamsynthese. I. Herstellung von 3,3‐Pentamethylen‐oxaziridin aus Cyclohexanon und Chloramin

Abstract: 3,3‐Pentamethylen‐oxaziridin 5, das als Isomeres des Cyclohexanon‐oxims für eine neue Synthese des Caprolactams Interesse besitzt, wird aus Cyclohexanon mit Ammoniak und Hypochlorit in 73proz. Ausbeute hergestellt, aus Cyclohexanon mit Chloraminlösung in 85proz. Ausbeute. Ein kristallines 1:1‐Addukt von Chloramin an Cyclohexanon 7 läßt sich in 91proz. Ausbeute zu 5 cyclisieren.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1977
1977
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Schmitz et al reported the preparation of oxaziridine 7 by reaction of cyclohexanone with ammonia and sodium hypochlorite. 27 A small amount of the N -chlorocyclohexanimine 8 is also formed in the reaction, but it does not affect typical synthetic applications of the N -H oxaziridine. N -Unsubstituted oxaziridines are highly reactive toward nucleophiles and are usually formed in situ in inert solvents and reacted further without additional purification.…”
Section: Synthesis and Physical Properties Of Oxaziridinesmentioning
confidence: 99%
See 1 more Smart Citation
“…Schmitz et al reported the preparation of oxaziridine 7 by reaction of cyclohexanone with ammonia and sodium hypochlorite. 27 A small amount of the N -chlorocyclohexanimine 8 is also formed in the reaction, but it does not affect typical synthetic applications of the N -H oxaziridine. N -Unsubstituted oxaziridines are highly reactive toward nucleophiles and are usually formed in situ in inert solvents and reacted further without additional purification.…”
Section: Synthesis and Physical Properties Of Oxaziridinesmentioning
confidence: 99%
“…Oxaziridines bearing unsubstituted nitrogen atoms are generally not synthesized by standard peracid oxidation methods due to the instability of N -H imines. Schmitz et al reported the preparation of oxaziridine 7 by reaction of cyclohexanone with ammonia and sodium hypochlorite . A small amount of the N -chlorocyclohexanimine 8 is also formed in the reaction, but it does not affect typical synthetic applications of the N -H oxaziridine.…”
Section: Synthesis and Physical Properties Of Oxaziridinesmentioning
confidence: 99%
“…3 Unfortunately, these two methods, although generally efficient, often generate a mixture of constitutional isomers. 4 Other ring-expansion 5 or rearrangement 6 reactions allow for the formation of 7-membered nitrogen-containing heterocycles from 3-, 4-, 5-, 6-, and 8-membered rings.…”
mentioning
confidence: 99%
“…spectra of (3a-j) indicates that these oxaziridines exist in solution as a single isomeric form, viz. cis (5) or trans (3). N-Alkyloxaziridines are configurationally stable at nitrogen at ambient temperature with large barriers to inversion (100-140 kJ m~l-').~O Accordingly the cis: trans isomer distribution of oxaziridines produced by the oxidation of N-alkyl imines is usually under kinetic control.…”
Section: Resultsmentioning
confidence: 99%